Attitudes to aging in midlife are related to health conditions and mood. (December 2014) - Thorpe, Anna M.; Pearson, John F.; Schluter, Philip J.; Spittlehouse, Janet K.; Joyce, Peter R.; Koopmans, Raymond; Rosness, Tor
ABSTRACT Background: Health is an important aspect of individuals' lives as they age. The aim of this study was to examine the relationship of sociodemographic factors, diagnosed chronic health conditions, and current depression with attitudes to aging in midlife. Methods: A cross-sectional baseline analysis was conducted on the first 300 participants from the Canterbury Health, Ageing and Life Course study in New Zealand, a stratified randomized community longitudinal study of adults recruited between 49 and 51 years. Attitudes were measured using the Attitudes to Aging Questionnaire (AAQ) and analyzed with a range of prevalent diagnosed chronic conditions, current depression, and sociodemographic variables. Results: Individuals perceived their physical aging more negatively after a diagnosis of hypertension, arthritis or asthma. Diagnosed lifetime depression and anxiety, and current depression, showed strong relationships with attitudes to aging across domains. After controlling for sociodemographic factors and current depression, individuals with diagnosed hypertension, arthritis, asthma, lifetime depression or anxiety continued to report significantly more negative attitudes to aging. Current depression showed the strongest associations with attitudes to aging and mediated relationships of health on attitudes to aging. Conclusions: Physical and mental health are related to attitudes to aging. Most chronic conditions examined are significantly associated with attitudes toward aging in the physical change domain. Diagnosed lifetime depression and anxiety, and current depression, are negatively related across attitudinal domains. Individuals can feel positive about aging while experiencing poorer health, but this is more difficult in the presence of low mood.